2006
DOI: 10.1097/01.dad.0000246646.45651.a2
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Vasculitis Update: Small Vessel Neutrophilic Vasculitis Syndromes

Abstract: A broad and diverse spectrum of vasculitic syndromes exists. These syndromes affect the skin with varying levels of associated systemic manifestations, running the gamut from a self-limited, localized, cutaneous phenomenon to rapidly progressive, multiorgan disease. The majority of cases of cutaneous vasculitis will show a neutrophilic small vessel vasculitis that can be either a primary (idiopathic) disorder (eg, cutaneous leukocytoclastic angiitis) or a secondary disorder that is associated with drugs, infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
153
1
32

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(187 citation statements)
references
References 244 publications
(410 reference statements)
1
153
1
32
Order By: Relevance
“…These two cases of vasculitis are the first to be reported that were temporarily related to inoculation using HIV-1 Env in combination with the saponin adjuvant QS21 in humans. The etiology of LCV is not well understood but has been shown to be associated with immune complexes, autoantibodies such as antineutrophil cytoplasmic antibody (ANCA), and inflammatory mediators particularly those associated with endothelial adhesion molecules [23,24]. In the general population, hypersensitivity vasculitis occurs in 10-30 cases per million/ year and 14 cases of Henoch-Schonlein purpura per million/year have been reported [23] with up to one-half being idiopathic in nature.…”
mentioning
confidence: 99%
“…These two cases of vasculitis are the first to be reported that were temporarily related to inoculation using HIV-1 Env in combination with the saponin adjuvant QS21 in humans. The etiology of LCV is not well understood but has been shown to be associated with immune complexes, autoantibodies such as antineutrophil cytoplasmic antibody (ANCA), and inflammatory mediators particularly those associated with endothelial adhesion molecules [23,24]. In the general population, hypersensitivity vasculitis occurs in 10-30 cases per million/ year and 14 cases of Henoch-Schonlein purpura per million/year have been reported [23] with up to one-half being idiopathic in nature.…”
mentioning
confidence: 99%
“…Proteolytic enzymes released by the neutrophils cause vessel wall damage and erythrocyte extravasation, resulting in palpable purpura [3]. Small, superficial vessel involvement can lead to urticarial lesions and purpura [7]. Deeper, dermal vessel involvement leads to hemorrhagic bullous or necrotic lesions [7].…”
Section: Discussionmentioning
confidence: 99%
“…Die aus Hautbiopsien bei AAV am häufigsten nachweisbare leukozytoklastische Vaskulitis allein ist jedoch wenig spezifisch und kann eine Vielzahl von Ursachen haben [24,38].…”
Section: Diagnostikunclassified